Comparison of clinical outcomes following vitrified warmed day 5/6 blastocyst transfers using solid surface methodology with fresh blastocyst transfers - K Muthukumar; Mohan S Kamath; Ann M Mangalaraj; T K Aleyamma; Achamma Chandy; Korula George (Wolters Kluwer Medknow Publications, 2013)
Objectives: The literature regarding clinical outcomes following day 5/6 vitrified warmed blastocysts transfer has been conflicting. We decided to evaluate and compare the clinical outcomes following vitrified warmed day 5/6 blastocyst transfer using a solid surface vitrification protocol with fresh blastocyst transfers. Settings: University teaching hospital. Study Design: A total of 249 women were retrospectively analyzed: 146 fresh day 5 blastocyst (group 1), 57 day 5 vitrified warmed blastocyst (group 2), and 46 vitrified warmed day 6 blastocyst (group 3) transfer cycles. Vitrification was done using solid surface methodology (non immersion protocol). The main outcomes were implantation rates, clinical pregnancy, and live birth rate per embryo transfer. Results: The baseline clinical characteristics were similar among all three groups. The implantation and clinical pregnancy rates following vitrified warmed day 6 blastocyst transfers (20.9% and 32.6%) were significantly lower as compared to day 5 fresh and vitrified warmed day 5 blastocyst transfers (40.3% and 56.1%, 36.3%, and 52.6%). However, there was no significant difference in the live birth rates across the three groups (group 1: 37.6%, group 2: 40.3%, and group 3: 28.2%). Conclusion: No statistically significant difference was observed in live birth rates between fresh day 5 blastocyst transfers and vitrified warmed day 5/6 blastocyst transfers. Vitrification of blastocysts using solid surface methodology is an efficient method of cryopreservation.